Watershed Morphometric Controls on Highland Flooding in Enrekang’s Urban Area - Sudirman Nganro; Safrudin Suaib Manyila; Muhammad Syahrir; Arifuddin Akil; Ramdania Tenreng; Andi Arifuddin Iskandar; Marsuki Marsuki; Cucu Nopita; Muhammad Abduh; Silfester Stevi Wandan (The Indonesian Journal of Planning and Development, 2026)
The earth's surface is completely divided by watersheds; urban and rural areas are sub-systems of watersheds. Flooding is influenced by climatic aspects, LULC, and morphometric characteristics. The Enrekang urban area is in the highlands. However, when it rains with high intensity, the area experiences flooding that causes social, economic, and environmental losses. This study aims to identify watersheds and reveal the morphometric factors of watersheds in the upstream part of the Enrekang urban area. The data used is NASADEM as a modernization DEM from SRTM, processed by spatial analysis techniques and mathematical calculations on the linear, areal, and relief aspects of the watershed. Data shows that in the Enrekang urban area, there is a confluence of the main stream (seventh-sixth order) from the upstream Saddang sub-watershed (SW-2) with the Mataallo sub-watershed (SW-3). In addition, the Rbm value of <3 indicates that the stream channel has a rapid rise in flood water levels, while the decline is slow. The value of the ruggedness number (Rn) parameter >2 is an extreme classification. High ruggedness number indicates steep slopes, and thus resulting in flash floods and erosion. In terms of area, the area of water catchment in the sub-watershed upstream of urban areas is 5,930.77 sq.km., the area is classified as a large watershed. A large catchment area will produce a large flood discharge. Factors of land use change in the upstream part, triggering an increase in surface runoff. There are three district capitals located upstream of Saddang watershed which causes the conversion of green land into built areas due to the need for housing and public facilities. This data can be a reference for the government, academics, and the community for the purpose of planning flood control programs in upstream of the Enrekang Urban Area.